APPLICATION OF COOPERATIVE LEARNING MODEL GROUP INVESTIGATION (GI) TYPE OF SOCIAL STUDIES IN IMPROVING LEARNING OUTCOMES IN ELEMENTARY SCHOOL STUDENTS - Acoci Acoci (Lambaga Jurnal dan Publikasi Universitas Muhammadiyah Buton, 2023)
The purpose of this study was to find out the application of the Group Investigation (GI) cooperative learning model for social studies subjects to improve the learning outcomes of fourth grade students at SD Negeri Wanco. One of the innovative learning models in order to improve and increase social studies learning outcomes for fourth graders of SD Negeri Wanco is through the Group Investigation (GI) Model. This research method uses the class action research method. Classroom Action Research follows a cyclical or recycling process starting from planning, action, observation and reflection. The object of research is 22 students. Data collection techniques carried out are: Tests, Interviews, and Observations. Data analysis was carried out by grouping data about learning outcomes during the learning process. The results of the study show that learning mastery in social studies subjects with the Group Investigation (GI) type cooperative learning model can improve learning outcomes in Social Sciences